Niveles de presión sonora y su incidencia en la salud de los habitantes del casco urbano de la ciudad de Calceta - Loor Lucas, Evelyn Guadalupe (2024)
The purpose of this research was to determine the incidence of sound pressure levels in the inhabitants of the urban area in Calceta city, based on 11 sampling points and three evaluation times (07:30 – 08:00; 12:30 – 1:00 p.m. and 16:30 – 17:00). Inductive, deductive and statistical methods were used, while the techniques were observation and survey. It is determined that all sampling points exceed the maximum limit of decibels (dB) established by the Unified Text of Secondary Environmental Legislation, highlighting P8 (P&S Gas Station) as the point that presented the greatest noise pollution (80.29 dB) at all evaluated times. Furthermore, it is evident through statistical analysis that at all times the noise level exceeds the maximum limits, presenting no significant statistical difference (p < 0.05). Based on the survey, it was determined that residents have mainly perceived headaches and hearing loss due to noise. Additionally, the city's hospital and the two health centers (Inés Moreno and San Bartolo) have reported conditions such as unspecified external otitis (H609), acute serous otitis media (H650), non-specific otitis media (H669), and infectious external otitis. In response to this, an action plan was designed and shared, focusing on measures to reduce noise pollution and preserve the environmental quality and health of the inhabitants in Bolívar canton.